Principles for good practice in participatory research: reflecting on lessons from the field - Vernooy, Ronnie; McDougall, C. (Routledge, 2003)
This chapter draws on case studies and literature to generate a number of ‘principles of good practices’ in participatory research in natural resource management. The intention is that these principles may be useful in the planning and assessment of the rigour of research methodologies.